Imaging of tumor viability in lung cancer: initial results using 23Na-MRI = Bildgebung der Tumor-Vitalität von Lungenkrebs - Henzler, Thomas; Konstandin, Simon; Schmid-Bindert, Gerald; Apfaltrer, Paul; Haneder, Stefan; Wenz, Frederik; Schad, Lothar R.; Manegold, Christian; Schönberg, Stefan; Fink, Christian (RöFo, 2012)
Purpose: 23Na-MRI has been proposed as a potential imaging biomarker for the assessment of tumor viability and the evaluation of therapy response but has not yet been evaluated in patients with lung cancer. We aimed to assess the feasibility of 23Na-MRI in patients with lung cancer. Materials and Methods: Three patients with stage IV adenocarcinoma of the lung were examined on a clinical 3 Tesla MRI system (Magnetom TimTrio, Siemens Healthcare, Erlangen, Germany). Feasibility of 23Na-MRI images was proven by comparison and fusion of 23Na-MRI with 1H-MR, CT and FDG-PET-CT images. 23Na signal intensities (SI) of tumor and cerebrospinal fluid (CSF) of the spinal canal were measured and the SI ratio in tumor and CSF was calculated. One chemonaive patient was examined before and after the initiation of combination therapy (Carboplatin, Gemcitabin, Cetuximab). Results: All 23Na-MRI examinations were successfully completed and were of diagnostic quality. Fusion of 23Na-MRI images with 1H-MRI, CT and FDG-PET-CT was feasible in all patients and showed differences in solid and necrotic tumor areas. The mean tumor SI and the tumor/CSF SI ratio were 13.3 ± 1.8 × 103 and 0.83 ± 0.14, respectively. In necrotic tumors, as suggested by central non-FDG-avid areas, the mean tumor SI and the tumor/CSF ratio were 19.4 × 103 and 1.10, respectively. Conclusion: 23Na-MRI is feasible in patients with lung cancer and could provide valuable functional molecular information regarding tumor viability, and potentially treatment response.